2023
DOI: 10.3390/jcm12072621
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Healthcare-Associated Infections in a Neonatal Intensive Care Unit before and during the COVID-19 Pandemic: A Four-Year Retrospective Cohort Study

Abstract: The COVID-19 pandemic may have had an impact on healthcare-associated infection (HAI) rates. In this study, we analyzed the occurrence of HAIs in a neonatal intensive care unit (NICU) of the Umberto I teaching hospital in Rome before and during the pandemic. All infants admitted from 1 March 2018 to 28 February 2022 were included and were divided into four groups according to their admission date: two groups before the pandemic (periods I and II) and two during the pandemic (periods III and IV). The associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…As for upper tract MDROs, our study showed a significant reduction in MSSA carriage. Contrarily, MRSA carriage significantly increased in NICU C, as a study performed by Meschiari et al showed a significant increase in the rate of MRSA, probably due to a clonal spread during the SARS-CoV-2 pandemic [38]; the same results were registered by Ceparano et al [39]. The rise in the carriage of MRSA during the pandemic period was probably due both to the high rate of empirical antibiotic use among infected patients, and to the reduction in active surveillance rates, isolation of MRSA carriers, and contact precautions by healthcare providers [26,40].…”
Section: Discussionsupporting
confidence: 64%
“…As for upper tract MDROs, our study showed a significant reduction in MSSA carriage. Contrarily, MRSA carriage significantly increased in NICU C, as a study performed by Meschiari et al showed a significant increase in the rate of MRSA, probably due to a clonal spread during the SARS-CoV-2 pandemic [38]; the same results were registered by Ceparano et al [39]. The rise in the carriage of MRSA during the pandemic period was probably due both to the high rate of empirical antibiotic use among infected patients, and to the reduction in active surveillance rates, isolation of MRSA carriers, and contact precautions by healthcare providers [26,40].…”
Section: Discussionsupporting
confidence: 64%